2023
DOI: 10.1108/ijebr-02-2023-0157
|View full text |Cite
|
Sign up to set email alerts
|

Gender stereotype perception, perceived social support and self-efficacy in increasing women's entrepreneurial intentions

Nizar Alam Hamdani,
Veland Ramadani,
Grisna Anggadwita
et al.

Abstract: PurposeWomen play an essential role in entrepreneurship because they have been able to make social and economic contributions in many countries. However, women continue encountering numerous difficulties when engaging in entrepreneurial activities, particularly from a societal perspective. Therefore, it is necessary to study the underlying factors influencing women's entrepreneurial intentions that lead to their success in entrepreneurship. This study examines gender stereotype perceptions, perceived social su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 106 publications
0
3
0
1
Order By: Relevance
“…It will increase in the case of female involvement in entrepreneurial activities. Hamdani et al (2023) concluded that social inclusion has a significant influence on women's entrepreneurial intention and that gender stereotypes and social support have a significant effect on self-efficacy. Stead (2017), analyzing the importance of belonging for women in an entrepreneurial context, identified five forms of performance of belonging by women (i.e., proxy, concealment, modeling the norm, tempered disruption, and identity-switching) because belonging for women entrepreneurs is a factor necessary for the development of self-efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…It will increase in the case of female involvement in entrepreneurial activities. Hamdani et al (2023) concluded that social inclusion has a significant influence on women's entrepreneurial intention and that gender stereotypes and social support have a significant effect on self-efficacy. Stead (2017), analyzing the importance of belonging for women in an entrepreneurial context, identified five forms of performance of belonging by women (i.e., proxy, concealment, modeling the norm, tempered disruption, and identity-switching) because belonging for women entrepreneurs is a factor necessary for the development of self-efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…PLS-SEM assesses the statistical significance of factor loadings and standardized regression coefficients between latent variables. The explanatory power of PLS-SEM models is evaluated using metrics such as the average R2 parameter, Goodness of Fit (GOF), Q2, and F2, which are commonly employed to gauge the predictive capability of PLS-SEM models in entrepreneurship studies [131,132]. The R2 parameter serves as an indicator of the predictive performance of the structural model [133].…”
Section: Discussionmentioning
confidence: 99%
“…That way, this study identifies critical conditions that shape the effects of resources. In so doing, we build on the literature that emphasises relative advantage in female social abilities and competences that enable female entrepreneurs to reach out and utilise the resources that are socially available (Emami et al, 2023;Hamdani et al, 2023), which helps us explain differences in growth aspirations, and the role of social resources in diminishing the gender gap.…”
Section: Introductionmentioning
confidence: 99%